Reingeniería de procesos de producción y comercialización para la empresa Carbón Burger de la ciudad de Loja - García Alejandro, Daniel Francisco (2015)
The present thesis is based in Reingeniería of or BPR (Business Process Reengenieering) like a management tool, the same one should be considered like a reaction to the change of the new realities of the companies, to develop it the technique of the observation was applied it stops later on to register the processes in a Record of Observation, to each process it represented it to him graphically, thanks to the flujogramas they were discovered the critical points clearly in the following processes: Process of Acquisition of Matter Prevails, Process of Preparation of the Meat, Process of Distribution and in the Process of Sale of the Hamburger, these processes required a lot of time in its majority, unnecessary steps, etc. For what the reingeniería is applied determining that it can decrease the costs and time and increasing the quality and speed, without this means a decrease of the quality. He/she conformed to a Team of Reingeniería, assigning the responsibility to each one of the areas of the company and integrated in the following way: General Manager: Diego Marizaca; Production: Rosa Gonzaga; Storage: José Luis Chamba; Commercialization: Malena Marizaca. Establishing a monthly meeting, with the purpose of evaluating the mapeo of the processes, discovering falencias, to redraw processes and elaboration of a budget. It could be carried out the mensuration of the processes, by means of the use of the comparative square of time, the processes made by the company Coal Burger of the city of Loja 651 minutes, with the redesign of the processes 293 minutes, obtaining this way a drastic decrease of 358 minutes. The implementation of the reingeniería requires of machines and teams in the Processes of Preparation of the Meat and Process of Sale of the Hamburgers, the sum of this investment is of $ 3.157,83. It is also necessary to indicate that it was done without of a worker, for what you can pay the investment with that surplus in 9 months ($ 3.186,00) Starting from the reingeniería it is possible to reduce the time in the processes with falencias, without this reduction means a decrease of the quality. It is indispensable that Reingeniería of Processes is applied in the company Coal Burger, with the purpose of reducing costs and the time, besides increasing the quality and the speed